Persistent Hypoglossal Artery: Challenges Associated With Carotid Revascularization. (October 2019) - Madden, Nicholas J.; Calligaro, Keith D.; Dougherty, Matthew J.; Maloni, Krystal; Troutman, Douglas A.
Anomalous connections between the anterior and posterior cranial circulation are rare embryologic entities. A persistent hypoglossal artery has a reported incidence of 0.03% to 0.09% and has been linked to intracranial aneurysms, atherosclerosis, and posterior circulation ischemia. Identification of this anomaly is essential prior to carotid artery revascularization given the technical challenges and added risks with intervention. We report a case of an 80-year-old female with progression of carotid stenosis in the setting of a persistent hypoglossal artery. We provide a review of the literature and discuss the technical challenges of carotid revascularization in this patient.